Redo surgery using IntraLase femtosecond laser for treating a decentered laser in situ keratomileusis flap. Issue 2 (February 2018) - Lei, Yulin; Hou, Jie; Zheng, Xiuyun
Objective: Decentered flaps are rarely reported after femtosecond laser-assisted in situ keratomileusis flap procedures. We present a patient with a decentered flap after preparation of a corneal flap using the Femto LDV technique. Methods: The 22-year-old man required a redo operation because of a decentered corneal flap. It was performed the same day at the patient's insistence and with his consent. The new corneal flap for the redo surgery was prepared using the femtosecond laser technique and IntraLase. Results: Uncorrected visual acuity for each eye was 1.2 during the 12-month follow-up. The results of the Femtosecond laser technique showed good predictability and repeatability regarding the preparation of corneal flaps, but it still may cause some intraoperative complications. Conclusion: Once redo surgery is needed, the size and depth of the initially prepared flap should be determined using anterior segment optical coherence tomography to pre-set the parameters for preparation of the redo flap.